Sistem Pendukung Keputusan Kinerja Guru Dengan Metode Analitycal Hierarchy Pada SMK Patriot Nusantara Jakarta - Sutarjo Sutarjo; Irwan Agus; Adhityo Kuncoro (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2023)
Patriot Nusantara Private Vocational High School (SMKS) is an educational institution in Jakarta, Patriot Nusantara SMKS organizes a teacher performance assessment program. In the process of assessing the performance of teachers at Patriot Nusantara Jakarta Vocational School, the conventional method is used by filling out a questionnaire carried out by the school principal and the assessment team, then the questionnaire is summarized. The large number of teachers makes it difficult for school principals and assessment teams to determine the best teacher decisions. To find patterns in teacher performance assessment, a decision support system was built, through research. This research uses the Analytical Hierarchy Process (AHP) method. This method is used to evaluate and make multi-criteria decisions. It evaluates various alternatives based on different criteria and assigns a relative score to each alternative. Based on the results of this research, it produces better and more accurate calculations. If previously selection took 1 day, now with the decision support system the selection time is shorter.